Analysis of disability indicators at spine and spinal cord injury in Ukraine in 2013 - Tarasenko, Oleg (Ukrainian Neurosurgical Journal, 2014)
The purpose. The study of disability indicators at injuries of the spine and spinal cord in 2013 in Ukraine. Materials and methods. Using specially developed program we studied disability indicators at spine and spinal cord injury on materials of medical and social expertise centers in 24 regions of Ukraine, Autonomous Republic of Crimea, Kyiv and Sevastopol in 2013. Results. The total number of patients with injury of the spine and spinal cord at whom primary disability was established in 2013 was in 2178, or 0.6 per 10 000 adult population. In most patients — 1368 disability group 3 was established, in 390 — group 2, in 420 — group 1. Disability was re-established in 6997 patients, or 1.9 per 10 000 adult population, that is 3.2 times higher than in patients at whom disability was primary established that confirms the duration, complexity and lack of efficacy of medical, professional, social and home rehabilitation. Conclusions. The highest rates of primary disability were marked in Kharkiv region, the lowest — in Sumy and Ternopil regions; highest rates of re-established disability — in Ivano-Frankivsk, the lowest — in Cherkassy region. We recommend to provide a joint clinical expert conference with participation of specialists in a field of neurosurgery, trauma, medical-social assessment to clarify the issues of disability examination at spine and spinal cord injury on the modern stage of development of medicine.